2014
DOI: 10.4071/imaps.422
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Thermal Management Solutions on PCBs for High Power Applications

Abstract: AbstractÀWith increasing power loss of electrical components, thermal performance of an assembled device becomes one of the most important quality factors in electronic packaging. Due to rapid advances in semiconductor technology, particularly in the field of high-power components, the temperature distribution inside of a component is a critical parameter of long-term reliability and must be carefully considered during the design phase.Two main drivers in the electronics industry are miniaturization and reliab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Our findings are in good agreement with previously reported results. 14,27,28 It is reported that FCLED samples exhibit much better thermal dissipation characteristics than lateral LEDs. 27,28 It is also found that the thermal conductivity of PCB, MCPCB, Si, ceramic and AlN substrates can be increased by using electroplated-copper-filled thermal vias (TVs), since the thermal path from the LED chip toward heat sink is shortened.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our findings are in good agreement with previously reported results. 14,27,28 It is reported that FCLED samples exhibit much better thermal dissipation characteristics than lateral LEDs. 27,28 It is also found that the thermal conductivity of PCB, MCPCB, Si, ceramic and AlN substrates can be increased by using electroplated-copper-filled thermal vias (TVs), since the thermal path from the LED chip toward heat sink is shortened.…”
Section: Methodsmentioning
confidence: 99%
“…14,27,28 It is reported that FCLED samples exhibit much better thermal dissipation characteristics than lateral LEDs. 27,28 It is also found that the thermal conductivity of PCB, MCPCB, Si, ceramic and AlN substrates can be increased by using electroplated-copper-filled thermal vias (TVs), since the thermal path from the LED chip toward heat sink is shortened. 28,29 To characterise the reliability of the packaged samples in sulfur ambient, the samples are loaded into a chamber, where humidity and temperature are set to be 75% and 25°C, respectively, with H 2 S gas (a concentration of 15 ppm).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding thermal management for PCB-based electronics, the existing macroscale approaches to controlling heat transport include the use of through-hole thermal vias in communication with large-area thick metal planes or cores [24], creating a cavity in the PCB to further reduce through-plane thermal resistance to a heat sink [24], using high thermal conductivity metal/graphite inlays [25], or novel PCB-based heat pipes [26]. Basic printed circuit board copper (Cu) plane layout for anisotropic thermal conductivity has also been exploited as a design strategy.…”
Section: Introductionmentioning
confidence: 99%
“…The LED technology is developing rapidly and more powerful LED devices placed in smaller packaging appear on the market, which must effectively dissipate large amounts of heat. [1] Heat negatively affects the performance and is a prerequisite for the emergence of failure, so proper thermal management is essential for the design of each LED device or system [2].…”
Section: Introductionmentioning
confidence: 99%